ANALISA AKIBAT PUTUSAN MAHKAMAH KONSTITUSI NOMOR 71/PUU-XIV/2016 TENTANG PENCALONAN KEPALA DAERAH MANTAN NARAPIDANA TERHADAP PENYELENGGARAAN PEMILU YANG DEMOKRATIS - Satyawasana, Ignatius Indra; Firdausy, Adriana Grahani (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This research aims to know the result of the ruling of the Constitutional Court the number 71/PUU-XIV/2016 candidature of head region ex-convict against the holding of democratic elections. The research method used is the type of legal normative The nature of the research perspective and applied. The research approach using the approach of legislation, a conceptual approach, and the approach to the case. The data source is primary data, secondary, and tertiary. Engineering data collection using the study of librarianship, engineering data analysis using the method of syllogisms. Based on the results of the research the author did, note that due to the ruling of the Constitutional Court the number 71/PUU-XIV/2016 candidature related head injury can convict the former area of democracy because local communities were not able to shift the candidates who could potentially do harm as well as doing the legal violations in the electoral competition.